2015
DOI: 10.1017/s1355617715000156
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Is Associated with Attenuated Frontostriatal Intrinsic Connectivity: A Preliminary Study

Abstract: Objective HIV-associated cognitive impairments are prevalent, and are consistent with injury to both frontal cortical and subcortical regions of the brain. The current study aimed to assess the impact of HIV infection on functional connections within the frontostriatal network, circuitry hypothesized to be highly vulnerable to HIV infection. Method Fifteen HIV-positive and 15 demographically matched control participants underwent 6 minutes of resting-state functional magnetic resonance imaging (RS-fMRI). Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 75 publications
10
63
1
Order By: Relevance
“…In a resting-state functional MR study (Ipser et al 2015), the HIV+ group ( n = 15), compared to the HIV– group ( n = 15), showed reduced dorsal caudate connectivity to frontal and parietal brain regions. Furthermore, reduced connectivity in the HIV+ group was observed between the dorsal caudate and dorsolateral prefrontal cortex, particularly in younger participants.…”
Section: Neuroimagingmentioning
confidence: 99%
“…In a resting-state functional MR study (Ipser et al 2015), the HIV+ group ( n = 15), compared to the HIV– group ( n = 15), showed reduced dorsal caudate connectivity to frontal and parietal brain regions. Furthermore, reduced connectivity in the HIV+ group was observed between the dorsal caudate and dorsolateral prefrontal cortex, particularly in younger participants.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Damage typically affects fronto-striatal structures and both structural and functional connectivity [13, 14] as well as hippocampal tissue [15] and motor areas [16, 17]. Abnormal fMRI pre-frontal activation during working memory tasks [18], increased measures of inflammation and diffusivity [19], and reduced resting state functional connectivity within the lateral occipital network [20], and overall cortical thinning [21, 22] have all been observed in HIV-positive adults relative to HIV-negative controls, and in many of these studies the structural changes were in excess of that to be expected given participant age.…”
Section: Pathology Of Central Nervous System (Cns) Hiv Infectionmentioning
confidence: 99%
“…One study found a number of structural and connectivity differences in brain regions heavily innervated by dopaminergic and cholinergic inputs, associated with HIV-status: decreased connectivity within the resting state fronto-striatal network (FSN), between FSN and caudate, and between the caudate and parietal regions relative to controls [14]. Diminished capacity for dopamine-mediated attention and reward processing, has also been shown in HIV-positive adults; researchers found reduced ability to ignore irrelevant information while processing a reward [79].…”
Section: Normal Cognitive Agingmentioning
confidence: 99%
“…Dopaminergic dysfunction (Lee et al 2009) and loss of midbrain dopaminergic projections to the BG (Beste et al 2010), in turn, affect motor functions and cognition via interconnected striatocortical and corticostriatal networks (Albin et al 1989; Betchen and Kaplitt 2003; Damier et al 1999). Because HIV, like PD, affects striatal structures (caudate nucleus, putamen), neurodegenerative processes in the aging HIV brain may be related to the same striatal-thalamo-cortical networks and dopaminergic abnormalities as in PD (Ipser et al 2015). Thus, neuronal degradation in dopaminergic midbrain structures and the BG have the potential to impede effective communication between subcortico-cortical network nodes, with consequences for attention, emotion, cognition, and motor control (Fig.…”
Section: Neural Mechanisms Of Functional Compromise In Hiv Infection mentioning
confidence: 99%
“…The asymptomatic (Antinori et al 2007) aging HIV-infected brain likely manifests in functional neuroadaptation that results in altered functional network connectivity. For example, a recent study found that HIV status and cognitive impairment was related with less DLPFC–dorsal caudate connectivity, and that the dorsal caudate was less connected to the executive network in HIV-infected individuals than controls (Ipser et al 2015). However, HIV patients diagnosed with more severe cognitive deficits, classified as HAND, performed poorly on visual attention tasks and did not show this compensatory increase in activation during task processing despite absence of structural brain compromise compared to HIV patients without evidence of cognitive decline.…”
Section: The Role Of Compensatory Mechanismsmentioning
confidence: 99%